Correlation Between Climate Variations and Rotavirus Diarrhea in Under-Five Children in Sidoarjo District Year 2016 – 2019 - Selena Vita Amanda; Laura Navika Yamani; Zayyin Dinana; Aussie Tahta Maharani; Erni Astutik; Noerfitri Noerfitri (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Rotavirus infection is one of the main causes of severe diarrhea and dehydration in toddlers. Climate variation is one of the factors that influence the outbreak of infectious diseases. This study aimed to clarify the relationship between climate variations and the incidence of rotavirus diarrhea among patients at the Soerya Mother and Child Hospital, Sidoarjo District in 2016 – 2019. Methods: This study used an ecological study with the Pearson correlation test. Rotavirus infection data was taken from the Viral Diarrhea Laboratory, Institute of Tropical Diseases, Universitas Airlangga, which was derived from fecal samples of patients with acute gastroenteritis with the unit of analysis at the individual level living in Sidoarjo district. Meanwhile, climate variation data were obtained from the Meteorology, Climatology, and Geophysics Agency Indonesia official website with units of analysis at the population level. Results and Discussion: The number of rotavirus diarrhea for 48 months as many as 149 cases with an average air temperature of 28.2â„ƒ, rainfall of 191.4 mm², humidity of 77.31%, and wind speed of 2.82 knots. There was a weak correlation between rainfall and the incidence of rotavirus diarrhea (p=0.01 r=0.367) and a weak correlation with humidity (p=0.016; r=0.347). Meanwhile, the air temperature (p=0.909 r=0.017) and wind speed (p=0.272 r=-0.162) had no relationship with the incidence. Conclusion: Rainfall and high humidity are factors associated with the prevalence of rotavirus diarrhea in children under-five years in the Sidoarjo District.